Role Conflict and Burnout among Administrators in Higher Institutions of Education in Uganda - Mbabazi, Faith; Wilson, Eduan; Ocheng, Mary Kagoire (East African Journal of Interdisciplinary Studies, 2023)
The purpose of this study was to find out the relationship between role conflict and burnout among administrators in higher education institutions in Uganda. There have been a number of studies on academicians in universities, but not much research has been done on administrators, especially in Uganda. The respondents included midlevel administrators such as deans, directors, heads of department, heads of sections, academic registrars, librarians, directors of services and human resource officers. This was a survey research design carried out on administrators in universities. The questionnaire, which was a combination of role conflict questions and Maslach burnout inventory, was administered to the administrators who had been randomly selected from universities. The findings indicated that role conflict was not a predictor of burnout dimensions of emotional exhaustion, cynicism and professional efficacy; however, coupled with demographics, the results changed, and there was a positive significant relationship, especially with age on emotional exhaustion. It was recommended that university top administrators should be interested in the mental state of their staff because, as earlier noted, emotional exhaustion was the most significant burnout dimension predicted by role conflicts